Influence of wood treatments on mechanical properties of wood-cement composites and of Populus Euroamericana wood fibers - Quiroga, A. (2015)
Woodecement composites are interesting materials for structural and isolation purposes. Dimensional stability, economic factors and resistance to environmental degradation are features that can be exploited for housing components. The main inconvenient affecting its manufacture is the incompatibility between wood and cement, caused by setting inhibitory substances present in woods. Wood treatments are multivariable processes required for the appropriate cement setting reaction on wood surfaces. Treatment conditions affect the mechanical properties of the resulting composites. This work evaluates the simultaneous influence of the variables ruling three widely used wood treatments e water extraction, degradation by alkaline hydrolysis and retention of inhibitory substances e on the mechanical properties of wood fibers and of resulting woodecement composites. Populus Euroamericana wood fibers and Portland cement were selected as case materials. The alkaline hydrolysis was found as the most effective treatment for the suppression of inhibitory substances and the highest decrease on mechanical properties of resulting composites. Empirical relationships describing the dependence of the compressive modulus of elasticity and compression strength of woodecement composites with the wood treatment variables are presented.